First Report on the Rapid Detection and Identification of Methicillin-Resistant Staphylococcus aureus (MRSA) in Viable but Non-culturable (VBNC) Under Food Storage Conditions - Ou, Aifen; Wang, Kan; Mao, Yanxiong; Yuan, Lei; Ye, Yanrui; Chen, Ling; Zou, Yimin; Huang, Tengyi (Frontiers in Microbiology, 2021)
Formation of viable but non-culturable (VBNC) status in methicillin-resistant Saphylococcus aureus (MRSA) has never been reported and it poses a significant concern for food safety. Thus, this study aimed to firstly develop a rapid, cost-effective, and efficient testing method for detection and differentiate MRSA strains in VBNC state, and further applied this in real food samples. Two targets were selected for detection of MRSA and toxin, and rapid isothermal amplification detection assays were developed based on cross-priming amplification methodology. VBNC formation was performed for MRSA strain in both pure culture and in artificially contaminated samples, then PMA treatment was further conducted. Development, optimization and evaluation of PMA-CPA were further performed on detection of MRSA in VBNC state. Finally, application of PMA-CPA was further applied for detection on MRSA in VBNC state in contaminated food samples. As concluded in this study, formation of VBNC state in MRSA strains has been verified, then 2 PMA-CPA assays have been developed and applied to detection MRSA in VBNC state from pure culture and food samples.